Establishment of regeneration system of Peucedanum praeruptorum and molecular association analysis of coumarin secondary metabolism - Tianliang, Liu; Liang, Wang; Yudan, Zhang; Yujiao, Zheng; Tao, Zhou; Luqi, Huang (Frontiers in Plant Science, 2025)
IntroductionPeucedanum praeruptorum is a medicinally critical species whose sustainable utilization is hindered by declining wild populations and insufficient cultivation systems. This study aimed to establish an optimized regeneration system for P. praeruptorum and elucidate the molecular mechanisms underlying coumarin biosynthesis, focusing on the roles of key phenylpropanoid pathway genes.MethodsLeaf, stem, and root explants were cultured on MS media supplemented with varying concentrations of 2,4-D, 6-BA, and IBA to induce callus, proliferation, differentiation, and rooting. Coumarin content (praeruptorins A, B, E) was quantified via HPLC, while RT-qPCR analyzed expression levels of PpPAL, PpC4H, and PpC2'H genes across tissues.ResultsOptimal media were identified: MS + 0.5 mg/L 2,4-D + 0.5 mg/L 6-BA (callus induction, 85.71% efficiency), MS + 1.0 mg/L 6-BA + 0.5 mg/L IBA (proliferation), and MS + 0.5 mg/L IBA (rooting, 69.44% success). Adventitious buds exhibited the highest total coumarin content (3.67× callus), with roots of seedlings accumulating 1.67× more coumarin than leaves. Expression of PpC2'H dominated across materials (PpC2'H > PpC4H > PpPAL), correlating strongly with coumarin levels.DiscussionThe study demonstrates that hormonal crosstalk (auxin-cytokinin balance) critically regulates morphogenesis, while PpC2'H acts as a bottleneck gene for coumarin synthesis. These findings enable targeted metabolic engineering (e.g., PpC2'H overexpression) to enhance yields, offering a sustainable alternative to wild harvesting.